Characteristics of traditional Chinese acidic rice soup (rice-acid) prepared with different fermentation methods - Na Liu; Likang Qin; Jihong Pan; Song Miao (Food Science and Human Wellness)
Rice-acid, a Chinese traditional acidic rice soup (rice-acid), is widely accepted by consumers due to its unique flavor and anti-oxidation, anti-aging and immunity enhancement functions. This study confirmed that L-lactic acid and malic acid were the main organic acids in rice-acid. Low-temperature rice-acid samples produced by enterprises had the highest signal intensity of sour taste. The total content of free amino acids in different fermented rice-acid samples were in the range of 0.003–0.468 mg/g. 42 key volatile flavor compounds were identified in rice-acid. 8 volatile compounds with a higher contribution to the aroma of rice-acid were respectively acetic acid, 1-octen-3-ol, 2-heptanol, ethyl acetate, propyl propionate, hexanal, nonanal, and 2,3-butanedione. The interaction between lactic acid bacteria (3.00 × 103–7.02 × 106 CFU/mL) and yeasts (5.04 × 104–2.25 × 108 CFU/mL) affected the formation of taste and aroma components in rice-acid. The physicochemical characteristics including titratable acidity, pH, reducing sugars, amino acid nitrogen, gamma-aminobutyric acid showed significant differences between low-temperature fermentation samples and high-temperature fermentation samples. In addition, relationships linking all data through Pearson coefficient correlation were also reported. In summary, the study can be used to improve the quality of rice-acid products.